The Brain in Cross-Cultural Adjustment: A Pilot Study of Japanese Expatriates Living in the United States - Keisuke Kokubun; Kiyotaka Nemoto; Yoshinori Yamakawa (Brain Sciences, 2025)
Background/Objectives: With the globalization of companies, the cross-cultural adjustment of expatriates working overseas is becoming an increasingly important topic. However, little research has been carried out on the brain, which is the source of the ability to adapt. Methods: Therefore, we conducted a pilot study on 10 expatriates working for Japanese local subsidiaries in the United States to analyze the relationship between their gray matter volume (GMV) measured by the Gray Matter Brain Healthcare Quotient and their cross-cultural adjustment and lifestyle. Results: As a result, in a partial correlation analysis controlled for demographic variables, there was a significant correlation between whole-brain GMV and general adjustment. A relationship was also shown between the local GMV of the default mode network and central executive network and interaction adjustment. Conclusions: This is the first pilot study to clarify the relationship between expatriates’ brain structure and cross-cultural adjustment, suggesting the effectiveness of a biological approach in cross-cultural adjustment research.